EDU KRISZA (KRITERIA JAJANAN SEHAT BEBAS ZAT ADITIF) KULINER LOKAL KUE BANJAR - Andhika Mayasari; Noer Af’idah; Oktaffi Arinna Manasikana (ABIDUMASY, 2021)
The characteristics of healthy snacks are containing healthy nutrition criteria, clean, and free from harmful additives, so it is safe to consume. Banjar cake is a sweet and crunchy cake made from glutinous rice flour with original flavors, chocolate and ginger. So, this community service entitled "Edu Krisza (criteria for healthy snacks free from additives), a typical Banjarese cake, culinary of Sumbernongko village". Some of the reasons why this Banjar cake has not become the main daily snack of the community are: 1) limited human resources, limited people who makes this Banjar cakes, because there is remain elder women only who can make Banjar cake in Nongko village, from 4 other villages; 2) Limited marketing including packaging factors and women who produce Banjar cake do not have ability in science and technology to promote; 3) limited consumers, which are only produced based on demands or certain events. These are the stages: 1) educational training on the criteria for healthy snacks free from additives; 2) Simulation of making Banjar cake; 3) Online marketing of Banjar cake through social media (Facebook, YouTube and Instagram).